Coprinopsis (Psathyrellaceae, Agaricales) in the Neotropics: three new species and a new combination - Schünemann, Bárbara Letícia Botura; Westphalen, Mauro; Díaz-Valderrama, Jorge Ronny; Aguilar, Vilma; Da Silveira, Rosa Mara Borges (Phytotaxa, 2023)
In order to contribute to the knowledge of Coprinopsis in Southern Brazil, specimens were collected in the Atlantic Forest and Pampa Biomes. Morphological studies and phylogenetic analyses (Maximum Likelihood and Bayesian Inference) of the nucITS, nucLSU, TEF1 and β-tubulin were performed to describe new species and their evolutionary relations. Five Coprinopsis species were found. The molecular and morphological data supported the description of three new species and a new combination in the genus. Detailed descriptions, illustrations of their macro- and microscopic characteristics and a key to identify Coprinopsis species in Brazil are provided.